Smart schools : better thinking and learning for every child - Perkins, David N. (New York : Free Press, 1995)
Offers systematic methods to help students to learn how to think, increase real understanding, and to perform more effectively.
Includes bibliographical references (p. 245-255) and index.
Library Journal.
Publisher's Weekly.
Adult.
Adult
Keywords: Comprehension; Learning, Psychology of; Thought and thinking -- Study and teaching -- United States; Memory; Psychololgy of learning; Thought and thinking -- Study and teaching